School truancy and welfare receipt dynamics in early adulthood: A longitudinal study - Collingwood, Patricia (Journal of criminology, 2023)
School truancy is associated with many negative life outcomes, including violent, property, and drug offending, lower levels of education, and subsequently lower status and lower-paying jobs. These negative life outcomes are also related to future reliance on government welfare payments. This research sought to identify how high school truancy affects young people's welfare receipt dynamics in emerging adulthood. It uses longitudinal data from a nationally representative household panel survey (the Household Income and Labour Dynamics in Australia Survey) to estimate the effect of truancy on young people's likelihood of receiving government-paid cash transfers in emerging adulthood. We find that young people who are truant are over four times more likely to receive cash transfers than young people who are not truant. Findings also show that the extent of truancy does not impact the likelihood of welfare receipt, even when differentiating between infrequent and problem truants. We conclude with some comments on truancy's role in welfare dynamics.